(3GdeLGdSIs - (3CHh HcQ CMeO Hf eQhGf GdeGdcj GdOjfhQis
(3ChdgG (B:s
(3CNHQfG GdTjN CHh GdMSf QTG Hf fXja QVi Gddg Yfg Yf CHj gQjQg Yf GdfHi Udi Gddg Ydjg hSde bGd cJH Gddg YR hLd Ydi cd faS MXkG ef GdRfG s
(3BNQgG (B:s
(3abGe YjSi aLdS ai GdTeS hbGd djS CfJ GdPi CbeJfi EfeG CbGefi GdPi de jQO Cf CUjH ef GdOfjG TjFkG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydjg SeGY SfI (B605 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1591s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs